1999
DOI: 10.1021/np9902744
|View full text |Cite
|
Sign up to set email alerts
|

Stilbene Derivatives from Cissus quadrangularis

Abstract: Three new stilbene derivatives, quadrangularins A, B, and C (2−4), have been isolated from the stems of Cissus quadrangularis, together with four known ones:  resveratrol, piceatannol, pallidol (1), and parthenocissine A (5). Structure elucidation of the new compounds was achieved using 2D NMR experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 6 publications
6
69
0
Order By: Relevance
“…natural products 21-24, see Fig. 5), [20][21][22][23] prompted Brill and Snyder to further investigate the structures of caraphenol B and C.…”
mentioning
confidence: 99%
“…natural products 21-24, see Fig. 5), [20][21][22][23] prompted Brill and Snyder to further investigate the structures of caraphenol B and C.…”
mentioning
confidence: 99%
“…[1] Several analogues of 1, compounds 2-6, have been obtained from other plants ( Scheme 1). [1,2] These molecules are all dimers or substituted dimers of resveratrol (7) with an indane skeleton. To date, no synthetic effort towards this family of compounds has been reported.…”
mentioning
confidence: 99%
“…Magano et al (2008) reported that the root extracts of S. italica subsp arachoides β-sitosterol, δ-amyrin, δ-amyrone, and flavonoids (quercetin) having different potential metabolic and physiological effects has also been reported to be present (Jainu and Devi, 2004;Jakikasem et al, 2000). There are also unique stilbene derivatives termed quadrangularins A, B and C (Adesanya et al, 1999). Phytochemical screening of the ethanolic extract of the stem of C. quadrangularis also revealed the presence of alkaloids, flavonoids, phenols and tannins in C. quadrangularis (Chidambara Murthy ).…”
Section: Discussionmentioning
confidence: 99%